Micro-Entrepreneurial Potential by Self-Producing Liquid Dishwashing Soap: Community Empowerment Through Green Accounting and MBKM Framework - Apollo apollo; Yudhi Herliansyah; Khozaeni bin Rahmad; Ismaanzira Ismail (Jurnal Pengabdian Masyarakat dan Penelitian Terapan, 2025)
This study presents the results of a community service program focusing on the empowerment of Indonesian migrant workers and micro-entrepreneurs in Penang, Malaysia, through the self-production of liquid dishwashing soap. The program integrated training in production, business management, and marketing, complemented by the introduction of green accounting practices. Using a participatory action research approach, the program was conducted over six months, involving workshops, mentoring, and digital marketing campaigns. Findings indicate that 80% of participants successfully produced liquid dishwashing soap independently, 70% adopted basic bookkeeping practices, and 50% expanded their market reach through social media. Average additional household income ranged from Rp 500,000 to Rp 800,000 per month. Moreover, the introduction of green accounting reframed environmental expenditures as long-term investments, fostering awareness of sustainability. The program contributes to both community development and institutional performance indicators under the Merdeka Belajar Kampus Merdeka (MBKM) framework, particularly IKU 3 (lecturer engagement outside campus) and IKU 6 (international collaboration). These results highlight the potential of micro-enterprises to improve socio-economic resilience when supported with integrated, sustainable approaches.